Tuberculous Osteomyelitis of Mandible: A Rare Case Report - Mishra, Ravish; Mall, B B; Kandel, Laxmi; Kandel, Santoh (Journal of Universal College of Medical Sciences, 2018)
Tuberculous osteomyelitis of mandible is an extremely rare condition, particularly in comparison to pyogenic infections and neoplastic diseases involving the mandible. Hereby we are reporting such type of case in a ten year old male, presented with draining sinus over right mandible since 3 months proved later as tuberculous osteomyelitis in absence of a primary focus and responded well to antitubercular treatment. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, Page: 59-62